Growth Performance of Labeo rohita and Gibelion catla against Different Oilseed Meal Based Diets in Semi-intensive Culture: Use of plant based diets in fish culture - Shafi, Javairia; Waheed, Kashifa Naghma; Zafarullah, Muhammad; Anum, Hafiza Fariha (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2018)
The present study was conducted to investigate efficacy of three different types of feeds formulated with low cost oil seed meal based proteins for growth of Labeo rohita and Gibelion catla cultured in semi-intensive system for 92 days. Formulated feeds incorporated soybean meal, guar meal and canola meal as major protein source with rice polish as control feed. Highest weight gain for L. rohita and G. catla was achieved with soybean meal based feed (121.8 g ± 4.02 g and 66.5 g ± 4.57 g) followed by canola meal based feed (107.5 g ± 17.1 g and 47.3 g ± 8.59 g), guar meal based feed (49.4 g ± 10.3 g and 19.6 g ± 8.55 g) and rice polish (31.8 g ± 1.40 g and 14.1 g ± 3.06 g), respectively. Growth performance of L. rohita was higher than G. catla in all treatments. During the experimental period, net production (kg/ tank) was 1.59 kg ± 0.07 kg, 6.02 kg ± 0.20 kg, 2.48 kg ± 0.52 kg and 5.37 kg ± 0.85 kg for L. rohita and 0.71 kg ± 0.15 kg, 3.32 kg ± 0.23 kg, 0.98 kg ± 0.43 kg and 2.37 kg ± 0.43 kg for G. catla achieved with rice polish, soybean meal, guarl meal and canola meal based feeds respectively. Results showed that soybean meal and canola meal based formulated diets can lead to higher fish growth and total fish production than other oilseed meals used in present investigation.